Characterization of Two Novel Bacterial Type A exo-chitobiose Hydrolases Having C-terminal 5/12-type Carbohydrate-binding Modules - Shariza, Jamek; Nyffenegger, Christian; Muschiol, Jan; Holck, Jesper; Meyer, Anne S.; Mikkelsen, Jørn D. (Springer Berlin Heidelberg, 2017)
Type A chitinases (EC 3.2.1.14), GH family 18, attack chitin ((1 → 4)-2-acetamido-2-deoxy-β-d-glucan) and chito-oligosaccharides from the reducing end to catalyze release of chitobiose (N,N′-diacetylchitobiose) via hydrolytic cleavage of N-acetyl-β-d-glucosaminide (1 → 4)-β-linkages and are thus “exo-chitobiose hydrolases.” In this study, the chitinase type A from Serratia marcescens (SmaChiA) was used as a template for identifying two novel exo-chitobiose hydrolase type A enzymes, FbalChi18A and MvarChi18A, originating from the marine organisms Ferrimonas balearica and Microbulbifer variabilis, respectively. Both FbalChi18A and MvarChi18A were recombinantly expressed in Escherichia coli and were confirmed to exert exo-chitobiose hydrolase activity on chito-oligosaccharides, but differed in temperature and pH activity response profiles. Amino acid sequence comparison of the catalytic β/α barrel domain of each of the new enzymes showed individual differences, but ~69% identity of each to that of SmaChiA and highly conserved active site residues. Superposition of a model substrate on 3D structural models of the catalytic domain of the enzymes corroborated exo-chitobiose hydrolase type A activity for FbalChi18A and MvarChi18A, i.e., substrate attack from the reducing end. A main feature of both of the new enzymes was the presence of C-terminal 5/12 type carbohydrate-binding modules (SmaChiA has no C-terminal carbohydrate binding module). These new enzymes may be useful tools for utilization of chitin as an N-acetylglucosamine donor substrate via chitobiose.